Cover Image, Volume 61, Issue 10. Issue 10 (13th September 2022) - Kumar, Robin; Maurya, Akhilendra K.; Parker, Kristopher D.; Kant, Rama; Ibrahim, Hend; Kabir, Md. Imtiazul; Kumar, Dileep; Weber, Annika M.; Agarwal, Rajesh; Kuhn, Kristine A.; Ryan, Elizabeth P.; Raina, Komal
Abstract : The cover image is based on the Research Article Gender‐based effect of absence of gut microbiota on the protective efficacy of Bifidobacterium longum‐fermented rice bran diet against inflammation‐associated colon tumorigenesis by Robin Kumar et al., https://doi.org/10.1002/mc.23452 .